METODE KONSELING INDIVIDU DALAM MENGATASI BOLOS SEKOLAH SISWA KELAS VIII SMPN 3 LENGAYANG SUMATERA BARAT (STUDI KASUS TERHADAP 1 SISWA) - ahmad putra (UIN Sunan Kalijaga Yogyakarta, 2019)
This study helps to understand what methods are used by counseling teachers in overcoming school skipping students. This research is descriptive qualitative with case study research. The data source of this study were two counseling teachers, namely Sartini Cut and Novrida Yanti and one class VIII student at SMPN 3 Lengayang West Sumatra. Data collection is done by interview method, and collection. The results of the study showed that the individual counseling method could overcome school absenteeism in the eighth grade students of SMPN 3 Lengayang West Sumatra by the directive, non directive and eclectic method. This third method is given twice to students and begins with directive counseling which is important is the guidance of counseling teachers, after that counseling is non-directive, namely students who are more suitable in discussing problems and eclectic counseling, while teachers with students are equally active in solving problems. With this method, the counseling teacher can make a diagnosis regarding the problems experienced by the student. Keywords: Individual Counseling, School Ballos